Early postnatal behavioral, cellular, and molecular changes in models of Huntington disease are reversible by HDAC inhibition - Siebzehnrubl, Florian A.; Reber, Kerstin A.; Urbach, Yvonne K.; Schulze-Krebs, Anja; Canneva, Fabio; Moceri, Sandra; Habermeyer, Johanna; Achoui, Dalila; Gupta, Bhavana; Steindler, Dennis A.; Stephan, Michael; Huu Phuc Nguyen,; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Huntington disease (HD) is an autosomal dominant neurodegenerative disorder caused by expanded CAG repeats in the huntingtin gene (HTT). Although mutant HTT is expressed during embryonic development and throughout life, clinical HD usually manifests later in adulthood. A number of studies document neurodevelopmental changes associated with mutant HTT, but whether these are reversible under therapy remains unclear. Here, we identify very early behavioral, molecular, and cellular changes in preweaning transgenic HD rats and mice. Reduced ultrasonic vocalization, loss of prepulse inhibition, and increased risk taking are accompanied by disturbances of dopaminergic regulation in vivo, reduced neuronal differentiation capacity in subventricular zone stem/progenitor cells, and impaired neuronal and oligodendrocyte differentiation of mouse embryo-derived neural stem cells in vitro. Interventional treatment of this early phenotype with the histone deacetylase inhibitor (HDACi) LBH589 led to significant improvement in behavioral changes and markers of dopaminergic neurotransmission and complete reversal of aberrant neuronal differentiation in vitro and in vivo. Our data support the notion that neurodevelopmental changes contribute to the prodromal phase of HD and that early, presymptomatic intervention using HDACi may represent a promising novel treatment approach for HD.
EVALuna2:36091